AN EPIDEMIOLOGICAL SURVEY OF FATAL RAILWAY TRACK ACCIDENT CASES IN GOA REGION (Journal of Forensic Medicine & Toxicology, 2022)
60 cases of fatal railway track accidents were brought for PM examination at Goa Medical College Bambolim Goa between 01/5/2016 to 30/4/2018 (Two Years). Data was analyzed with respect to age, sex, month wise distribution of cases, location of bodies, injury pattern etc. Many were Male subjects and predominantly unknown male. Majority of cases were brought by Konkan Railway Police Station. 21-30years age group was commonly affected. Many subjects were found on main line. Majority of cases were accidental in nature and laceration was the most common type of mechanical injury finding. Subarachnoid hemorrhage was common among subjects. Head injury was common cause of death. Liver was most commonly affected organ among abdominal injury cases. Cervical spine transaction was very common among spinal transaction.
Keywords: fatal railway track accidents; head injury